Indications and Results of Ankle Arthroscopy in Vietnam - Dung Tran Trung; Manh Nguyen Huu; Thai Nguyen Hoang (Archives of Sports Medicine and Physiotherapy - Peertechz Publications, 2017)
Objectives:1.Evaluate the result of ankle arthroscopy;2.Evaluate the surgical indication and technique of ankle arthroscopy. Patients and methods:retrospective research 40 patients underwent ankle arthroscopy in Saint Paul University Hospital and Hanoi Medical University Hospital. Results:70% male patients,average age is 41.9± 18.5. 50% impingement,40% OCD lesion and 10% old ankle fracture. Evaluate the results with Olerud Molander with increasing score at least 10 points,all patients satisfied with the results. Conclusion:Ankle arthroscopy give good result